The Emerging Role of Myeloid-Derived Suppressor Cells in Tuberculosis - Magcwebeba, Tandeka; Dorhoi, Anca; du Plessis, Nelita (Frontiers in Immunology, 2019)
Myeloid cells are crucial to host control of Mycobacterium tuberculosis (M.tb) infection, however the adverse role of specific myeloid subsets is increasingly appreciated. Relevance of such cells for therapeutic strategies and predictive/prognostic algorithms is promoting interest in the role of innate regulatory myeloid cells in tuberculosis (TB). Myeloid-derived suppressor cells (MDSC) are a heterogeneous collection of phagocytes comprising of monocytic- and polymorphonuclear cells that exhibit potent suppression of innate- and adaptive immune responses. Accumulation of MDSC under pathological conditions associated with chronic inflammation, most notably cancer, is well described. Evidence supporting the involvement of MDSC in TB is increasing, yet their significance in this infection continues to be viewed with skepticism, primarily due to the lack of genetic evidence unequivocally discriminating these cells from other terminally differentiated myeloid populations and the complex nature of MDSC. In this review we highlight recent advances in MDSC characterization and summarize findings on the TB-induced hematopoietic shift associated with MDSC expansion. Lastly, the mechanisms of MDSC-mediated disease progression and future research avenues in the context of TB therapy and prophylaxis are discussed.